Peru : Report on the Observance of Standards and Codes (ROSC) Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2004)
The public sector in Peru is clearly distinguished from the rest of the economy, but the existence of various legal and statistical definitions of the government makes it difficult to demarcate it clearly from the rest of the public sector. The recent constitutional reform has strengthened the decentralization process, but key fiscal aspects have yet to be defined. The current distribution of fiscal responsibilities between the central government and local governments is legally defined, but the allocation of expenditure responsibilities and intergovernmental transfers need further clarification.